Grouping Diabetes Diagnosis Based on Age Range with K-means Algorithm - Allwin M.Simarmata; Maria Albina Pratiwi Sianipar; Sukbinder Singh; Intan Is Mutiara Gulo (Institute of Computer Science (IOCS), 2021)
Diabetes Mellitus has two types of disease, namely Diabetes Type I and Diabetes Type II. Research on the grouping of diabetes based on age at RSU Royal Prima Medan has not been carried out. For this reason, the researchers made a research analysis in grouping diabetes based on age. The aim of this research is to find the age group that is susceptible to being diagnosed with Type I or Type II diabetes. Researchers took sample data from patients diagnosed with diabetes of 2019 as many as 200 data. The method used in grouping the data is Kmeans. The Kmeans method has been widely used in various studies for grouping in the medical field. The results of the calculation analysis show that a sample of 200 data is Type I Diabetes at the age of 43 - 47, 56, 62, 67, 68 while Type II diabetes is at the age of 49, 55, 63. It is possible from the results of the study that patients of that age are not based on There are not many types though. The conclusion in this study is that the grouping of Type I and Type II diabetes based on age is expected to assist the hospital in identifying patients quickly so that patients can receive health services quickly as well.